A Combination of Diabetic Foot Exercise and Foot Massage on Ankle Brachial Index on Patients with Type 2 Diabetes Mellitus - Suharyo Hadisaputro; Muhammad Arif Ramadhan; Hotma Rumahorbo (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Diabetes Mellitus (DM) is a chronic metabolic disorder that genetically and clinically includes the heterogenic manifestation of insulin lost and high risk of hyperglycemia, atherosclerosis, and vascular disease. 4 pillars of type II diabetes management include education, diet, physical exercise and pharmacologic intervention. One of the non-pharmacology treatments is diabetic foot exercises and foot massage on Ankle Brachial Index on patients with type 2 diabetes mellitus. This study aims to assess the effect of effective diabetic foot exercise and foot massage on the Ankle Brachial Index on patients with type 2 diabetes mellitus in Srondol public health, Semarang. This study is quasi-experimental studies using pretest-posttest control group design. Moreover, this study also organizes two groups involving the intervention group with diabetic foot exercise and foot massage combination as well as a control group with a foot massage. Purposive sampling technique is used to obtain 28 respondents who are divided into two groups. Wilcoxon sign rank test result shows p-value = <0.05, meaning that there is an effect of diabetic foot exercise and foot massage on the Ankle Brachial Index between intervention and control groups on patients with type 2 diabetes mellitus.